The USE OF QUIZIZZ AS A DIGITAL-BASED FORMATIVE ASSESSMENT TOOL IN ENGLISH LANGUAGE TEACHING - Dea Amelia Asmarani; Rafika Anwar (Research on English Language Education, 2025)
This study explores the use of Quizizz as a digital-based formative assessment tool in English Language Teaching (ELT). The research aims to analyze how Quizizz supports student engagement, motivation, and assessment efficiency. Employing a qualitative approach through library research, data were collected from scholarly journals, books, and credible online sources. Descriptive-analytical methods were used to examine Quizizz's features in relation to formative assessment principles. Findings reveal that Quizizz enhances student participation through gamification, real-time feedback, and automated scoring. It also fosters motivation and self-reflection, supporting a student-centered learning environment. Moreover, the platform improves assessment efficiency by reducing grading time and providing instant insights. The study concludes that Quizizz is not just a game-based platform but a strategic educational tool aligned with formative assessment objectives. It is recommended that teachers integrate Quizizz to enhance learning experiences and instructional practices in modern ELT settings.